Enriched cocoa pod composts and their fertilizing effects on hybrid cocoa seedlings - Chris Fidelis; B. K. Rajashekhar Rao (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Composting has the potential to recycle wastes as a means of conserving natural resources. The study was aimed at examining feasibility of producing nutrient-enriched composts from pest infested cocoa pods with chemical amendments and using manure composts as a fertilizing material in cocoa seedling nursery. Methods Cocoa pod waste was composted in static vessels, aerobically, with chemical enrichments (triple super phosphate charged at 0.4% P or urea charged at 0.8% N or poultry manure charged at 22%) along with a control at the Cocoa and Coconut Institute, Papua New Guinea. The reaction (pH) of the composting mixtures (pH) and macronutrients dynamics was monitored at periodic intervals. Effect of soil incorporation of cocoa pod manure composts at 10 g kg-1 was assessed on the growth and foliar concentration of macro-nutrients in hybrid cocoa seedlings. Results In the finished manure composts, dry matter loss ranged from 30.6 to 63.3%; greatest in composting mixtures charged with super phosphate and poultry manure. Besides, super phosphate enriched mixture lost small fraction of initial N (6.6%) compared to un-enriched cocoa pod waste (30.2%). Composting mixtures with greater pH values during composting process showed higher losses of N. Super phosphate charged manure compost outperformed the control, in terms of C/N ratio and concentration of macro-nutrients (P, K, Ca, Mg and S). Quality parameters for all the manure composts conformed to the Canadian Compost Guidelines indicating satisfactory standards. Waste cocoa pods enriched with superphosphate did not show any deleterious effects on cocoa seedlingsâ growth, rather, improved plant height, dry matter production and foliar N concentration. Conclusion Waste cocoa pods, co-composted with triple super phosphate and poultry manure, produced composts of desirable quality and can be effectively used to fertilize the cocoa seedlings.